2015
DOI: 10.1513/annalsats.201407-312oc
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults with Chronic Lung Disease Report Less Limitation Compared with Younger Adults with Similar Lung Function Impairment

Abstract: Rationale: Disability guidelines are often based on pulmonary function testing, but factors other than lung function influence how an individual experiences physiologic impairment. Age may impact the perception of impairment in adults with chronic lung disease. Objectives:To determine if self-report of physical functional impairment differs between older adults with chronic lung disease compared with younger adults with similar degrees of lung function impairment. Methods:The Lung Tissue Research Consortium pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
0
16
1
Order By: Relevance
“…Older patients (age ≥65 years) had significantly lower total SGRQ scores than younger patients (age <65 years), indicating better health status. 38 However, older adults in the Lung Tissue Research Consortium had better lung function as measured by FEV 1 , FVC, and diffusing capacity of the lungs for carbon monoxide and similar 6-minute walk distance compared with younger adults, whereas older patients in the current study had worse lung function and decreased exertional tolerance. Similarly, results from the Subpopulations and Intermediate Outcome Measures in COPD Study demonstrated that patients over age 65 years had better quality of life compared with patients age 50-64 years.…”
Section: Discussioncontrasting
confidence: 54%
“…Older patients (age ≥65 years) had significantly lower total SGRQ scores than younger patients (age <65 years), indicating better health status. 38 However, older adults in the Lung Tissue Research Consortium had better lung function as measured by FEV 1 , FVC, and diffusing capacity of the lungs for carbon monoxide and similar 6-minute walk distance compared with younger adults, whereas older patients in the current study had worse lung function and decreased exertional tolerance. Similarly, results from the Subpopulations and Intermediate Outcome Measures in COPD Study demonstrated that patients over age 65 years had better quality of life compared with patients age 50-64 years.…”
Section: Discussioncontrasting
confidence: 54%
“…Moreover, an awareness of chronic diseases could also affect emotional disorders [ 40 ]. In particular, middle-aged adults have many roles in social and familial activities; therefore, disease awareness at an early age of onset, role limitations, and impairments may cause a number of psychological problems [ 41 43 ]. The depressive symptoms associated with chronic diseases have various causes, such as the increased risk of complications [ 4 ], increased economic loss due to healthcare utilization and cost [ 44 ], increased functional disabilities [ 45 ], limitations of physical activity [ 8 ], and loss of productive work time [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with findings from studies of the general population and persons with other chronic diseases, including fibromyalgia, 20 gastroesophageal reflux, 21 HIV infection, 22 and breast cancer. 23 Using data from patients with chronic lung diseases (advanced COPD and interstitial lung diseases), Berry et al 3 recently found that older adults had lower odds of reporting health-related limitations. Our investigation, restricting the population to COPD, confirmed a similar pattern of differences.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Studies of HRQL in COPD show that, independent of lung function, younger adults tend to report worse scores than do older adults, suggesting a pattern of more negative perception of health among younger subjects. 3,4 Little is known about the reasons for these differences and how they may impact the provision of care in COPD.…”
mentioning
confidence: 99%